2017
DOI: 10.1159/000480524
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcome after Intracranial Hemorrhage Related to Non-Vitamin K Oral Anticoagulants

Abstract: Background: Intracranial hemorrhage (ICH) is a serious, life-threatening, but fortunately rare complication of non-vitamin K oral anticoagulant (NOAC) therapy. There are limited data on NOAC-related ICH prognosis. Methods: All consecutive patients admitted to a single center due to acute NOAC-related ICH from September 2012 until the beginning of 2017 were included. Risk factors, type of NOAC, and location of ICH were evaluated. Risk for ischemic and bleeding events and clinical status upon admission and at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Sixteen studies provided individual patient data of 53 patients with ICH ( 6 – 8 , 10 , 12 , 13 , 15 24 ), whereas six case series reported results on, overall, 394 patients ( 1 , 2 , 5 , 9 , 11 , 14 ). Two studies ( 1 , 24 ) included patient data that have been previously reported ( 7 , 8 ). In order to avoid any duplication, in this study, we only included the data from the most recent reports ( 1 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies provided individual patient data of 53 patients with ICH ( 6 – 8 , 10 , 12 , 13 , 15 24 ), whereas six case series reported results on, overall, 394 patients ( 1 , 2 , 5 , 9 , 11 , 14 ). Two studies ( 1 , 24 ) included patient data that have been previously reported ( 7 , 8 ). In order to avoid any duplication, in this study, we only included the data from the most recent reports ( 1 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…A small number of patients did not allow for firm conclusions. On the other hand, a relatively high number of reported case series and case reports were published in the following years (1,2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%